The potential of agroforestry concessions to stabilize Amazonian forest frontiers: a case study on the economic and environmental robustness of informally settled small-scale cocoa farmers in Peru. (March 2021) - Pokorny, Benno; Robiglio, Valentina; Reyes, Martin; Vargas, Ricardo; Patiño Carrera, Cesar Francesco
Highlights: In Peru, agroforestry concessions address farmers encroaching forests. The vast majority of encroaching farmers don't have a robust livelihood basis. There is little linkage between economic success and environmental consciousness. Cacao farmers do not show a better environmental performance than other farmers. Recognition of land tenure is only a meaningful first step to stabilize frontiers. Abstract: Agroforestry Concessions, foreseen by the new Peruvian Forest Law, anticipate integrating thousands of small-scale farmers encroached on public forest land into the formal economy, to strengthen local livelihoods, stimulate land restoration, and halt deforestation. But, there are contrasting opinions regarding the potential of agroforestry and land tenure security to create economically and environmentally robust livelihoods. To better understand the relevance of this potential, this study analyses the economic and environmental robustness of 118 informally settled small-scale cocoa farmers in three districts in the Peruvian Amazon. The study shows that the vast majority of these farmers faced serious obstacles to overcome. Less than 20 % of the households have managed to establish economically robust livelihoods on a robust natural production basis. Farm size, specialization in cocoa, and participation in associations positively influenced the economic performance of the households but had little effect on the quality of natural resource management and on the capacity to conserve forests. To harness the potential of cocoa farming requires long-term support well adapted to local specificities. The legal recognition of sustainable land-use practices on public forest land is a meaningful step. To effectively address deforestation, however, requires broader integrated approaches that go far beyond the promotion of sustainable land-uses.